PENTINGYA PENDAMPINGAN PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA KRISTEN - Lestimar Sihombing; Triana Apriliyanti; Jois Nababan; Grace Clarita Rutwati Panjaitan; Triwati Lase (JURNAL BEATITUDES, 2023)
The family is the center for the development of all activities. In the family everyone is free to develop each of their respective gifts. In the family the foundation of children's life is built and developed. Family is a safe place to take shelter when there are storms in life. Maybe other people often don't understand the difficulties of life that are felt but in our family we get attention and protection. The family is a place to transfer values, a living laboratory for each family member and learn good things from each other. The family is a place where problems arise and solutions. There is no family that does not face life's problems. Often problems arise unexpectedly. For example, husband-wife relationships, problems faced by teenage children, and economic problems. However, families who let Christ reign as Lord over their lives can definitely solve all problems. The method used is important lectures and discussions on assisting Christian religious education in Christian families. All stages have been carried out properly supported by high congregational participation